M-CSF Priming of Osteoclast Precursors Can Cause Osteoclastogenesis-Insensitivity, Which Can be Prevented and Overcome on Bone - De Vries, Teun J.; Schoenmaker, Ton; Aerts, David; Grevers, Lilyanne C.; Souza, Pedro P. C. [UNESP]; Nazmi, Kamran; Van De Wiel, Mark A.; Ylstra, Bauke; Van Lent, Peter L.; Leenen, Pieter J. M.; Everts, Vincent (Wiley-Blackwell, 2015)
Osteoclasts and macrophages share progenitors that must receive decisive lineage signals driving them into their respective differentiation routes. Macrophage colony stimulation factor M-CSF is a common factor; bone is likely the stimulus for osteoclast differentiation. To elucidate the effect of both, shared mouse bone marrow precursor myeloid blast was pre-cultured with M-CSF on plastic and on bone. M-CSF priming prior to stimulation with M-CSF and osteoclast differentiation factor RANKL resulted in a complete loss of osteoclastogenic potential without bone. Such M-CSF primed cells expressed the receptor RANK, but lacked the crucial osteoclastogenic transcription factor NFATc1. This coincided with a steeply decreased expression of osteoclast genes TRACP and DC-STAMP, but an increased expression of the macrophage markers F4/80 and CD11b. Compellingly, M-CSF priming on bone accelerated the osteoclastogenic potential: M-CSF primed cells that had received only one day M-CSF and RANKL and were grown on bone already expressed an array of genes that are associated with osteoclast differentiation and these cells differentiated into osteoclasts within 2 days. Osteoclastogenesis-insensitive precursors grown in the absence of bone regained their osteoclastogenic potential when transferred to bone. This implies that adhesion to bone dictates the fate of osteoclast precursors. Common macrophage-osteoclast precursors may become insensitive to differentiate into osteoclasts and regain osteoclastogenesis when bound to bone or when in the vicinity of bone. J. Cell. Physiol. 229: 210-225, 2014. (c) 2014 Wiley Periodicals, Inc.